The GREEN RESTAURANTS: A STRATEGY FOR PROMOTING ECO-GASTRONOMY TOURISM IN VOJVODINA’S CITIES - Todorovic, Milorad (Turizam, 2025)
The concept of green restaurants has a significant impact on the promotion of eco-gastronomy tourism. This research investigates the potential of green restaurants as a sustainable tourism strategy with the objective of enhancing the appeal of urban tourist destinations in Vojvodina. The survey was carried out between February and November 2024 in restaurants located in four urban destinations within the Autonomous Province of Vojvodina (Novi Sad, Subotica, Sombor, and Zrenjanin), with a total of 287 respondents participating. The research findings showed a connection between attitudes towards gastronomy tourism and green restaurants, as well as between the importance of green practices and attitudes towards these types of restaurants. In addition, knowledge and interest in gastronomy significantly influence their desire to visit destinations with green restaurants. The results suggest that promoting green restaurant initiatives could position the cities of Vojvodina as competitive destinations for eco-gastronomy tourism.